From colour to cure: unveiling the antimicrobial power of plant pigments - Mat Ali, Qurratu Aini; Mohd Hatta, Farah Ayuni; Othman, Rashidi; Mohtar, Mastura (Nova Science Publishers, Inc., 2026)
Plant pigments, including carotenoids, chlorophyll, and betalains, are a diverse group of compounds with unique chemical structures that contribute to their vibrant colours and potential antimicrobial properties. These properties have found applications in the food industry for extending the shelf life of perishable goods and enhancing food safety. Moreover, the incorporation of plant pigment extracts or derivatives into pharmaceutical formulations holds promise for combating drug-resistant microbes. This study investigated the antimicrobial efficacy of selected plant pigments using minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) assays. Chlorophyll, extracted from green algae (Chlorella vulgaris; C. vulgaris), exhibited a potent bactericidal activity against both Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) at a concentration of 2.5 µg/µL. Similarly, bixin, extracted from annatto (Bixa orellana L.) seeds, also exhibited bactericidal activity by effectively inhibiting S. aureus and E. coli at concentrations of 5 µg/µL and 2.5 µg/µL, respectively. In contrast, the remaining four plant extracts required concentrations of ≥ 5 µg/µL to inhibit the growth of both microbes. These findings highlight the potential of natural pigments as sustainable alternatives to synthetic antibiotics, offering a multitude of benefits beyond their colour. Further research is crucial to unravel the complex relationship between the structural diversity of plant pigments and their antimicrobial activity.